ABCB1/4 gallbladder cancer risk variants identified in India also show strong effects in Chileans. (April 2020) - Boekstegers, Felix; Marcelain, Katherine; Barahona Ponce, Carol; Baez Benavides, Pablo F.; Müller, Bettina; de Toro, Gonzalo; Retamales, Javier; Barajas, Olga; Ahumada, Monica; Morales, Erik; Rojas, Armando; Sanhueza, Verónica; et al.
Highlights: Genetic variants in ABCB1 /4 are associated with gallbladder cancer risk in Chileans. Conferred risk effects and allele frequencies were similar in Chile and North India. Chileans with large proportions of Mapuche ancestry showed strong associations. Abstract: Background: The first large-scale genome-wide association study of gallbladder cancer (GBC) recently identified and validated three susceptibility variants in the ABCB1 and ABCB4 genes for individuals of Indian descent. We investigated whether these variants were also associated with GBC risk in Chileans, who show the highest incidence of GBC worldwide, and in Europeans with a low GBC incidence. Methods: This population-based study analysed genotype data from retrospective Chilean case-control (255 cases, 2042 controls) and prospective European cohort (108 cases, 181 controls) samples consistently with the original publication. Results: Our results confirmed the reported associations for Chileans with similar risk effects. Particularly strong associations (per-allele odds ratios close to 2) were observed for Chileans with high Native American (=Mapuche) ancestry. No associations were noticed for Europeans, but the statistical power was low. Conclusion: Taking full advantage of genetic and ethnic differences in GBC risk may improve the efficiency of current prevention programs.